Implementation of a customised antimicrobial resistance laboratory scorecard in Cameroon, Ethiopia and Kenya - André Trollip; Renuka Gadde; Tjeerd Datema; Kamau Gatwechi; Linda Oskam; Zachary Katz; Andrew Whitelaw; Peter Kinyanjui; Patrick Njukeng; Dawit A. Wendifraw; Ibrahimm Mugerwa; Grace Najjuka; et al. (AOSIS, 2022)
Background: In low-resource settings, antimicrobial resistance (AMR) is detected by traditional culture-based methods and ensuring the quality of such services is a challenge. The AMR Scorecard provides laboratories with a technical assessment tool for strengthening the quality of bacterial culture, identification, and antimicrobial testing procedures. Objective: To evaluate the performance of the AMR Scorecard in 11 pilot laboratory evaluations in three countries also assessed with the Stepwise Laboratory Quality Improvement Process Towards Accreditation (SLIPTA) checklist. Methods: Pilot laboratory evaluations were conducted in Cameroon, Ethiopia and Kenya between February 2019 and March 2019. Assessors with previous SLIPTA and microbiology experience were trained. Assessors performed the laboratory assessments using the SLIPTA and AMR Scorecard tools. Results: Weaknesses in technical procedures and the quality management systems were identified in all areas and all laboratories. Safety had the highest mean performance score (SLIPTA: 68%; AMR Scorecard: 73%) while management review had the lowest (SLIPTA: 32%; AMR Scorecard: 8%) across all laboratories. The AMR Scorecard scores were generally consistent with SLIPTA scores. The AMR Scorecard identified technical weaknesses in AMR testing, and SLIPTA identified weaknesses in the quality management systems in the laboratories. Conclusion: Since the AMR Scorecard identified important gaps in AMR testing not detected by SLIPTA, it is recommended that microbiology laboratories use SLIPTA and the AMR Scorecard in parallel when preparing for accreditation. Expanding the use of the AMR Scorecard is a priority to address the need for quality clinical microbiology laboratory services in support of optimal patient care and AMR surveillance.